A framework for analyzing monetary policy in an economy with e-money - Yu Zhu; Scott Hendry (Bank of Canada, 2019)
This paper considers an economy where central-bank-issued fiat money competes with privately issued e-money. We study a policy-setting game between the central bank and the e-money issuer and find (1) the optimal monetary policy of the central bank depends on the policy of the private issuer and may deviate from the Friedman rule; (2) there may exist multiple equilibria; (3) when the economy approaches a cashless state, the central bank's optimal policy improves the market power of the e-money issuer and can lead to a discrete decrease in welfare and a discrete increase in inflation; and (4) first best cannot be achieved. Central-bank-issued e-money leads to a simple optimal policy that achieves the first best.
Keywords: E52; 330; Digital currencies; Monetary policy